ANALYSIS OF VOLCANO RISK ASSESSMENT CASE STUDY GUNTUR VOLCANO -WEST JAVA - SUMINAR (NIM: 2241300); Tim Pembimbing: Dr. Irwan Meilano, M.Sc.; Asep Saepuloh, Dr. Eng., WULAN
The Indonesian archipelago is geographically a place of three major plates of the earth, Eurasian Plate, the Indo-Australian Plate and the Pacific Plate. Associated with the eruption of volcanoes, one of the technologies that can be used is the remote sensing technology. Guntur volcano in West Java filed as the study site because of its location adjacent to a fairly dense residential population and the increasing development of infrastructure, especially related to tourism in the surrounding Garut area. The data based on remote sensing data consists of optical satellite imagery form ASTER (Advanced Spaceborne Thermal Emission and Reflection Radiometer) Level-1A, Landsat 8 - OLI (Onboard Operational Land Imager ), ASTER GDEM as an input parameter hazards of volcanic (pyroclastic flow , pyroclastic fallout, lava and lava), slope, surface brightness temperature, and vegetation density . Data such as population density, distributed according neighborhood and area residents woke up on the land cover map as an input parameter of vulnerability, as well as interviews, surveys and field observations with sampling grid as an capacity parameter. Overall the data is projected on the coordinate system WGS 1948 49 S. Retrieved risk index values range between 0.04 to 0.5, which is identified as a zone of high risk index of 0.4 to 0.5, moderate risk index of 0.3 to 0.39, zoning low risk index of 0.2 Ã‚Â– 0.29, zone risk index is very low to no risk of 0.04 to 0.19 . area which has a high risk index value has meaning those areas exposed to the dangers of a high index value, the condition of high vulnerability and low capacity conditions.